Percutaneous Neutralization Screw with Arthroscopic Bone Grafting for Scaphoid Nonunion - Sivakumar, Brahman Shankar; Ang, Soon Ghee; Smith, Nicholas (Journal of Wrist Surgery, 2024)
Background The optimal management of established scaphoid nonunion is undecided. Priorities in this setting include the restoration of normal geometry and elimination of any bony defect, provision of adequate stability to allow early mobilization, and the achievement of union.Technique We describe a technique of arthroscopic assessment and debridement, reduction of deformity and autologous cancellous bone grafting, and stabilization via a specifically designed neutralization screw, to realize the above aims.Materials and Methods Consecutive patients undergoing this technique at a single center in Sydney, Australia, underwent pre- and postoperative assessment. Parameters assessed include a range of motion and patient-reported outcome measures.Results In total, 14 patients (11 males and 3 females with a mean age of 22.4 years) underwent treatment of scaphoid nonunion using this technique, at a mean of 105.9 weeks following index injury. The cohort was followed up radiologically for a mean of 20.7 weeks and clinically for 147.3 weeks. Union was achieved in 13 of 14 patients at a mean of 12.4 weeks. Significant improvements were noted in pain visual analogue scale (VAS), while changes were also noted in range of motion and quick disabilities of arm, shoulder and hand (QuickDASH) score.Conclusion This technique of arthroscopic management of scaphoid nonunion using a neutralization screw and cancellous bone graft is simple, easily reproducible, and confers numerous advantages when compared with other treatment modalities.
Keywords: scaphoid; non-union; arthroscopy; screw fixation; bone grafting